Analysis of Online Learning and Its Relationship with Learning Motivation of Cosmetology Students - Julita Novriwanti; Rahmiati Rahmiati (Universitas Negeri Padang, 2022)
Online learning is learning that uses the internet network with accessibility, connectivity, flexibility, and the ability to bring up various types of learning interactions. Makeup is one of the courses that conduct online learning at the Department of Make-up and Beauty. This study aims to describe the online learning process, learning motivation, and to determine the relationship between online learning and student motivation in the make-up course of the Department of Make-up and Beauty, Padang State University. This research is a type of descriptive quantitative research. The data collection instrument used in this study was a questionnaire (questionnaire) distributed via Google Form, data analysis used Descriptive Percentage analysis. The research sample was students majoring in Makeup and Beauty, Faculty of Tourism and Hospitality, Padang State University class of 2019 session A-F. The results obtained are 1) Online learning with an average score of 56.22 and a percentage of 7 respondents (12.7%) having very high learning, 15 respondents (27.2%) having high learning, 27 respondents ( 49.0%) have moderate learning and 6 respondents (10.9%) have low consumptive behavior. Classified in the high category, 2) Students' learning motivation of the Department of Makeup and Beauty, Padang State University with an average score of 56.82 and a percentage of 6 respondents (10.9%) having very high motivation, 19 respondents (34.5% ) have high motivation, 21 respondents (38.1%) have moderate motivation, 9 respondents (16.3%) have low motivation. Classified in the moderate category, 3) There is a significant positive relationship between online learning and learning motivation of students of the Department of Makeup and Beauty, Padang State University at a significant level of 5% with an rcount value of 0.997 > rtable 0.266 and the correlation level is included in the very strong category.